Job Stressors and Turnover Intention of Information Technology Executives in Malaysia: The Mediating Role of Employee Well-Being - ., NASEEBULLAH (2018)
Information Technology (IT) has emerged as an essential element in developing countries such as Malaysia in supporting the need for regular, real-time, and dependable information in business and industry. The Malaysian government set a target to be a more developed country as a part of Vision 2020, which called for enabling information and communication technology (ICT) to transform Malaysia into a knowledge-based industrial society.